Relations between shyness and assertiveness traits with the dimensions of the five factor model - Bratko, Denis (Array, 2002)
Five-factor model (Costa & McCrae, 1992) represents comprehensive framework for organizing individual differences into five broad dimensions: neuroticism, extraversion, openness to experience, agreeableness and conscientiousness. Lower-level personality traits are expected to be correlated with these dimensions. The purpose of this study was to explore the relations among shyness, assertiveness and dimensions of the five-factor model. Sample of 336 high school students (124 males and 212 females) completed self-report version of the NEO-FFI (Costa & McCrae, 1992), as well as the shyness/assertiveness questionnaire (Zarevski & Vukosav, 1997). Shyness and assertiveness were highly correlated. Results revealed complex pattern of relations between the five-factor personality model and shyness and assertiveness. The predictive power of the NEO-FFI was better for shyness (R2=.35) than for assertiveness (R2=.16), despite the similar reliabilities of these scales. The regressions of the shyness and assertiveness on the five dimensions were higher in the females than in males. Extraversion, agreeableness and neuroticism were significant predictors of assertiveness both in male and female samples. However, the predictors for shyness were different. Extraversion was the only predictor in the males, while extraversion, neuroticism and agreeableness significantly predicted female shyness.